Manajemant Breast Engogerment Kompres Daun Kubis Dingin (Brassica Oleracea Var. Capitata) dan Breastcare terhadap Pembengkakan Payudara pada Ibu Nifas - Yusita, Intan; Yuliani, Meda; Hayati, Ning (Universitas Batanghari Jambi, 2024)
Breast milk duct dams and swelling of the mammary glands are one of the lactation problems that occur after childbirth and during breastfeeding. Breast swelling occurs when the milk ducts do not drain completely and narrow. Milk thickens and the lumen of the milk ducts is blocked. From 3 to 6 days after birth until the milk is expelled normally, symptoms such as warmth, pain to the touch, tenderness, and swelling associated with breast swelling will appear. From 3 to 6 days after birth until the milk is expelled normally, symptoms such as warmth, pain to the touch, tenderness, and swelling associated with breast swelling will appear. The use of cabbage leaves for the treatment and prevention of breast swelling is very simple, the inside of cabbage leaves can be put in the freezer for approximately 20-30 minutes before the procedure. Place cold cabbage leaves inside your bra for 30 minutes and do it twice a day for 3 days. This study aims to determine the difference in effectiveness before and after cabbage leaves (Brassica Oleracea Var.Capitata) and Breast Care in Reducing Breast Swelling. This research is a quasi-experimental design research with one group pre and post design research methods. The population in this study was 34 postpartum mothers who experienced breast swelling on day 3 to day 14. The results of the Wilcoxon test found differences in breast swelling scores before and after applying cold cabbage leaf compresses and breastcare, so it can be concluded that there is a statistically significant average difference between breast swelling scores before and after treatment, where the mean after treatment decreased by 1.15 compared to the mean before treatment 2.79. This means that giving cold cabbage leaf compresses and breastcare can effectively reduce the problem of breast swelling in puerperal mothers. Applying cabbage leaf compresses (Brassica Oleracea var. Capitata) cold and Breast Care combined with very effective in reducing breast swelling in puerperal mothers.